Evolution of teaching in short-term courses: A systematic review - Andrés F. Mena-Guacas; María F. Chacón; Aura Patricia Munar; Marizol Ospina; Maryuri Agudelo (Heliyon, 2023)
Short-term courses are a useful tool for continuous training to update and deepen knowledge in various fields. In this article, we analyse the evolution of the teaching methods used in short-term courses through a systematic review conducted using the PRISMA methodology. The inclusion criteria for selecting articles were those that described the methodological structure of the teaching methods used in designing short-term courses. The exclusion criteria were courses longer than 90 days and unfinished documents. The search was conducted on April 9, 2022, using the SCOPUS database. The list of papers was reviewed and analysed three times by different researchers to ensure that they met the criteria. Articles approved by at least two researchers were selected. The results were systematically analysed based on criteria that allowed us to understand the learning methods used, such as the educational modality, content presentation, teaching methodology for teamwork and individual work, technological resources, and assessment methods. We selected 42 articles, and the results are presented in four parts: the learning experience, teaching methodology, technological resources, and assessment methods. One of the main findings is that short-term courses are primarily designed for experiential learning, and memory-related activities commonly used in traditional training are not typically included in short-term courses.